Linking ethical leadership to nurses’ internal whistleblowing through psychological safety - El-Gazar, Heba Emad (Nursing ethics, 2025)
Background: Cultivating internal whistleblowing among nurses is of paramount importance to nurse leaders. Yet, the literature on how nurse leaders can foster this phenomenon among nurses is limited. Additionally, the underlying mechanisms linking leadership behaviors to internal whistleblowing intentions remain underexplored.Aim: This study aimed to examine how ethical leadership is linked to internal whistleblowing intentions among nurses through the mediating effect of psychological safety.Research design: A multicenter cross-sectional research design was used for this study.Participants and research context: This study involved 201 nurses working in three tertiary governmental hospitals across three cities in Egypt. Data were collected between October and December 2023, using an introductory information form, the Ethical Leadership Scale, the Psychological Safety Scale, and the Internal Whistleblowing Intentions Scale. Structural equation modeling was used to evaluate study hypotheses.Ethical consideration: Research Ethics Committee of Faculty of Nursing, Port Said University, Egypt approved the study (reference number: NUR (6/8/2023)(28)), and each participant signed the informed consent form before participation in the study.Results: Ethical leadership was positively linked to nurses’ psychological safety and internal whistleblowing intentions. Psychological safety mediated the link between ethical leadership and nurses’ internal whistleblowing intentions.Conclusion: Our study suggests that nurse leaders can foster nurses’ intentions to blow the whistle internally by adopting ethical leadership behaviors and enhancing psychological safety among nurses.